Analysis of Molecular Concentration and Brightness from Fluorescence Fluctuation Data with an Electron Multiplied CCD Camera - Unruh, Jay R. (The Biophysical Society, 2008)
We demonstrate the calculation of particle brightness and concentration from fluorescence-fluctuation photon-counting statistics using an electron-multiplied charge-coupled device (EMCCD) camera. This technique provides a concentration-independent measure of particle brightness in dynamic systems. The high sensitivity and highly parallel detection of EMCCD cameras allow for imaging of dynamic particle brightness, providing the capability to follow aggregation reactions in real time. A critical factor of the EMCCD camera is the presence of nonlinearity at high intensities. These nonlinearities arise due to limited capacity of the CCD well and to the analog-to-digital converter maximum range. However, we show that the specific camera we used (with a 16-bit analog-to-digital converter) has sufficient dynamic range for most microscopy applications. In addition, we explore the importance of camera timing behavior as it is affected by the vertical frame transfer speed of the camera. Although the camera has microsecond exposure time for illumination of a few pixels, the exposure time increased to milliseconds for full-field illumination. Finally, we demonstrate the ability of the technique to follow concentration changes and measure single-molecule brightness in real time in living cells.